Integrating water resources and power generation: The energy–water nexus in Illinois - DeNooyer, Tyler A.; Peschel, Joshua M.; Zhang, Zhenxing; Stillwell, Ashlynn S. (Applied energy, 2016)
[Display omitted] •We quantify the water withdrawal and consumption for power generation in Illinois.•A shift from coal to natural gas decreases water withdrawal and consumption.•Simulated closed-loop cooling decreases withdrawals, but increases consumption.•Moderate water prices can economically motivate cooling system retrofits. Thermoelectric power plants contribute 90% of the electricity generated in the United States. Steam condensation in the power generation cycle creates a need for cooling, often accomplished using large amounts of water. These large water requirements can lead to negative consequences of power plants dialing down or shutting down during times of low water availability. Consequently, water constraints can translate into energy constraints. Projected future population growth and changing climate conditions might also increase the competition for water in many areas, motivating a resource accounting analysis to both establish a baseline of current water requirements and simulate possible impacts from future water and energy management decisions. Our analysis of the current water demands for power generation, focused on the state of Illinois, combined existing digital spatial datasets with engineering basic principles to synthesize a geographic information systems (GIS) model of current and projected water demand for thermoelectric power plants. We evaluated two potential future cases based on water use implications: (1) a shift in fuel from coal to natural gas, and (2) a shift in cooling technology from open-loop to closed-loop cooling. Our results show that a shift from coal-generated to natural gas-generated electricity could decrease statewide water consumption by 0.10billionm3/yr (32% decrease) and withdrawal by 7.9billionm3/yr (37% decrease), on average. A shift from open-loop to closed-loop cooling technologies could decrease withdrawals by an average of 21billionm3/yr (96% decrease), with the tradeoff of increasing statewide water consumption for power generation by 0.18billionm3/yr (58% increase). Furthermore, we performed an economic analysis of retrofitting open-loop cooling systems to closed-loop cooling, revealing an annual cost between $0.58 and $1.3billion to retrofit the 22 open-loop cooling plants considered, translating to an effective water price between $0.03 and $0.06/m3. The synergies and tradeoffs between water resources and power generation yield interesting implications for integrated decision making and policy in Illinois and elsewhere.